Argonaute 2: A Novel Rising Star in Cancer Research - Ye, ZhenLong (J Cancer, 2015)
AGO2 (Argonaute 2, EIF2C2) is the only member in AGO family with catalytic activity and of extreme importance during small RNAs guided gene silencing processes. The structural investigations have provided insights into details and functional mechanisms of the four major domains within AGO2. As a multifunction player, AGO2 has been revealed involved in tumorgenesis through miRNAs-dependent or independent ways. And nowadays, AGO2 has also been more importantly found ectopically over-expressed in carcinomas and closely associated with aspects of cancers in means of interacting with well-known tumor factors. Here, we provide a review on structural insights, functional mechanisms, novel roles and relationship with carcinomas of AGO2.